Presence of indicator bacteria, Shiga toxin-producing Escherichia coli, and nontuberculous mycobacteria in oregano - VELAZQUEZ-MEDELLIN, Alan Ricardo; HERNANDEZ-MIXTECO, Margarita; CASTRO-MORALES, Oscar; GOMEZ-SANTIAGO, Fabian; CARREÑO-DURAN, Luis Ramon; CODIZ-HUERTA, Maria Guadalupe; RIVERA-GUTIERREZ, Sandra; HELGUERA-REPETTO, Addy Cecilia; CAMPOS-PEÑA, Victoria; CERNA-CORTES, Jorge Francisco (Food Science and Technology, 2023)
Limited data are available regarding microbial contamination in oregano. This study aimed to evaluate the microbiological quality and presence of diarrheagenic Escherichia coli pathotypes and nontuberculous mycobacteria (NTM) in 85 oregano samples purchased from different markets in Mexico City. All samples analyzed were positive for aerobic-mesophilic bacteria, with limits ranging from 1.14 to 6.5 log CFU/g. A total of 67, 41, and 9 samples were positive for total coliforms, fecal coliforms, and E. coli, respectively, present at concentrations ranging from <3 to >1,100 MPN/g. One sample harbored Shiga toxin-producing E. coli strains positive for the Shiga toxin 2 (stx2) locus at a concentration of 3 MPN/g. NTM species were recovered from 15 samples and included M. fortuitum (six), M. smegmatis (two), M. conceptionense (one), M. porcinum (one), M. parafortuitum (one), M. flavescens (one), M. goodii (one), and two strains that could not be identified. Measures to diminish the high levels of microorganisms and pathogenic bacteria in this food item might be advisable. Good hygiene practices, good manufacturing practices, and hazard analysis and critical control points must be applied throughout the chain of production to ensure the safety of oregano.